Patterns of dissolved organic matter across the Patagonian landscape: A broad-scale survey of Chilean and Argentine lakes - Zagarese, Horacio Ernesto (2017)
Dissolved organic matter (DOM) is a complex mixture of carbon compounds from autochthonous and allochthonous sources. Dissolved organic carbon (DOC) concentrations and optical metrics of DOM provide clues as to the sources and processes affecting the DOM pool. Herein we provide the first broad-scale characterisation of DOM from Patagonian lakes across a strong west-east precipitation gradient. Fifty-eight lakes from Northern Patagonia (Argentina and Chile) plus six lakes from the Antarctic Peninsula were sampled during summer 2000-01. Six DOM metrics were evaluated: DOC absorbance at 254nm (a254) and 350nm (a350), DOC-specific absorbance at 254nm (a254/DOC) and 350nm (a350/DOC) and spectral slope between 275 and 295nm (S275-295). The DOM of Chilean maritime lakes and shallow (<15m) Andean lakes exhibited terrestrial signatures and a pattern of variation consistent with their occurrence across the longitudinal precipitation gradient (i.e. S275-295 increased, whereas a350/DOC decreased from west to east). The contribution of allochthonous DOM was smaller in deep (>15m) Andean lakes, which is consistent with their longer water retention time. Steppe lakes, mostly from endorheic basins, made up the most heterogeneous group with regard to DOM characteristics.